Data Protection Based on the Hadith “Prohibition Against Taking Another Person’s Stick” in the Digital Age - Nofa Isman (Technology and Society Perspectives (TACIT), 2026)
The protection of personal data is increasingly being discussed in research, with most studies addressing it from the perspectives of maqasid al-sharia and hifdz an-nasf, even though the legal basis for this protection can be explained through qiyas aulawi using the hadith about the walking stick. This study aims to (1) explain the urgency of personal data protection in the digital age, (2) explain the hadith prohibiting the taking of another person’s walking stick, and (3) explore personal data protection in the digital age through the qiyas aulawi method. The method used is a qualitative approach involving library research with a descriptive methodology. The results of this study are, first, the importance of safeguarding personal data in the digital age because it can lead to identity theft and misuse of information. Second, the “cane hadith” is classified as hasan; its content establishes that the fundamental legal principle regarding property is that it is haram to take it without the owner’s permission, even if the property is of little value—whether between fellow Muslims or non-Muslims. This demonstrates that Islam highly respects and protects private property rights from all forms of infringement. Third, the application of qiyas aulawi based on the hadith prohibits the use of another person’s personal data without their permission. By applying the findings of this study, every individual can easily engage in digital transactions by sharing only non-private information, and no one will use another person’s personal data without permission; furthermore, the application of qiyas in the digital age is highly necessary.